3D Prosthodontics Wire Bending Mechanism With A Linear Segmentation Algorithm - Abdul Hamid, Rahimah; Ito, Teruaki (Penerbit UTeM, 2016)
This study proposes the idea of automated 3D wire bending mechanism which is flexible and capable of making any type of bend for dentistry applications.Till recently, wire bending in orthodontics and prosthodontics applications has been manually bent by a skillful dental technician.Manual wire bending has a huge tendency to create errors,thus affecting the efficiency of the wire for the specified treatment,in parallel with the elongation of the treatment time.Besides,it can simultaneously increase the bending time due to some additional major adjustments and leads to bender fatigue. In general,the accuracy of the bend is inconsistent and depends on many factors,mostly on the expertise of the bender.Hence,due to these limitations in the manual wire bending and some urgency to decrease the dependency on the bender’s competency,this article introduces a theoretical framework of the 3D linear segmentation algorithm to realize the proposed bending mechanism.